Optimal renewal of definite integrals of monotone functions from the class $H^{ω}$ - Busarova, T. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain an exact estimate of the error of optimal renewal of an integral on a set of functions $f(t)$ monotone on $[a, b]$ with a convex majorant of the modulus of continuity, provided that $|f(b) − f(a)| = L > 0$.